2019
DOI: 10.1136/gutjnl-2018-317479
|View full text |Cite
|
Sign up to set email alerts
|

GABRP regulates chemokine signalling, macrophage recruitment and tumour progression in pancreatic cancer through tuning KCNN4-mediated Ca2+ signalling in a GABA-independent manner

Abstract: Background and aimsPancreatic ductal adenocarcinoma (PDAC) is a leading cause of cancer-related death worldwide. Neurotransmitter-initiated signalling pathway is profoundly implicated in tumour initiation and progression. Here, we investigated whether dysregulated neurotransmitter receptors play a role during pancreatic tumourigenesis.MethodsThe Cancer Genome Atlas and Gene Expression Omnibus datasets were used to identify differentially expressed neurotransmitter receptors. The expression pattern of gamma-ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 51 publications
3
86
0
Order By: Relevance
“…Sung et al found that GABRP enhances aggressive phenotype of ovarian cancer cells (58). Jiang et al found that the expression of GABRP in pancreatic cancer tissues was significantly increased and associated with poor prognosis, contributing to tumor growth and metastasis (59). In our study, we found that the expression of GABRP in cancer tissues was higher than in adjacent normal tissues and high expression of GABRP are associated with poor prognosis of patients with COAD, which were consistent with the previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Sung et al found that GABRP enhances aggressive phenotype of ovarian cancer cells (58). Jiang et al found that the expression of GABRP in pancreatic cancer tissues was significantly increased and associated with poor prognosis, contributing to tumor growth and metastasis (59). In our study, we found that the expression of GABRP in cancer tissues was higher than in adjacent normal tissues and high expression of GABRP are associated with poor prognosis of patients with COAD, which were consistent with the previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Particularly, the presence of symbiosis between macrophages and tumor cells has been shown by experiments where coculture of these cells caused the degradation of collagen [44]. Previous study has shown that macrophage recruitment plays a key role in GABRP-mediated tumor progression in pancreatic cancer [45]. TAMs also involved in tumor growth in glioblastoma [45,46].…”
Section: Discussionmentioning
confidence: 96%
“…Promote tumor angiogenesis and lymphangiogenesis in TME [51,52] Regulate the function of neutrophil in TME [45] Positively related to the risk of metastasis [62,63,72] Recruit immune cells -Recruit neutrophils in TME and metastatic niche [30,[42][43][44][45] -Recruit granulocytes to promote the formation of early metastatic microenvironment [40,49] -Promote MDSCs infiltration in TME [47,48] -Positively related to the extent of macrophage infiltration in TME [50] Promote cell proliferation of primary tumors [26,[54][55][56][57] Abbreviations: CXCL5, CXC motif ligand 5; TME, tumor microenvironment; MDSC, myeloid-derived suppressor cell.…”
Section: Functions Of Cxcl5 Referencesmentioning
confidence: 99%
“…A low expression of CXCL5 in tissues has been found to reduce the recruitment of tumor-associated lymphocytes [9]. Also, CXCL5 has been associated with the degree of macrophage infiltration in primary organs, participating in innate immune responses and is considered important for immunotherapy [50].…”
Section: Functions Of Cxcl5 Referencesmentioning
confidence: 99%